2017
DOI: 10.1039/c7ra04332e
|View full text |Cite
|
Sign up to set email alerts
|

Computational assignments of lattice vibrations of ice Ic

Abstract: Herein,viathe first-principles density functional theory, CASTEP code, we investigated the 15 vibrational normal modes of ferroelectric hydrogen-ordered phase of ice Ic and the two peaks of hydrogen bond are clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 48 publications
3
43
1
1
Order By: Relevance
“…Morrison and Jenkins [29] suggested that the splitting of the optical modes is due to the coupling with the intramolecular stretching vibrations. In our previous study, the existence of two basic H-bond vibrational modes was first established in ice Ic [30]. These two peaks are contributed by the two fundamental vibrations of H-bonds, the two-bond mode and the four-bond mode.…”
Section: Resultsmentioning
confidence: 90%
“…Morrison and Jenkins [29] suggested that the splitting of the optical modes is due to the coupling with the intramolecular stretching vibrations. In our previous study, the existence of two basic H-bond vibrational modes was first established in ice Ic [30]. These two peaks are contributed by the two fundamental vibrations of H-bonds, the two-bond mode and the four-bond mode.…”
Section: Resultsmentioning
confidence: 90%
“…The mechanism of H-bond vibrations was the central topic in our previous studies [25,26,27,28,29]. We found two basic H-bond vibration modes in ice Ic, which gave rise to two triangular peaks in INS [27]. In all ice phases, each water molecule is linked with four neighbors via H-bonds to form a tetrahedral structure.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the lengths of the H-bonds in ice XVI are bigger than Ih, manifesting an obvious red-shift of the H-bond (for the upmost mode, 314 cm −1 vs. 327 cm −1 ), and a slight blue-shift in the stretching region [25]. In the translational region, two H-bond peaks were found similar to the spectrum of ice Ic [27]. These H-bond vibrations could be classified into two groups based on their physical motions.…”
Section: Discussionmentioning
confidence: 99%
“…There are four H-bonds linked with one molecule to form a tetrahedral structure in ice crystals. For ice Ic, there are two kinds of vibration modes for one molecule: two H-bonds vibrating mode and four H-bonds vibrating mode with a strength ratio of [ 33 ]. These two types of modes were also observed in the ice XIV crystal lattice.…”
Section: Resultsmentioning
confidence: 99%